Resurrection plants optimize photosynthesis despite very thick cell walls by means of chloroplast distribution. (23rd January 2021) - Nadal, Miquel; Perera-Castro, Alicia V; Gulías, Javier; Farrant, Jill M; Flexas, Jaume
Abstract: Resurrection plants are vascular species able to sustain extreme desiccation in their vegetative tissues. Despite its potential interest, the role of leaf anatomy in CO2 diffusion and photosynthesis under non-stressed conditions has not been explored in these species. Net CO2 assimilation ( A n ) and its underlying diffusive, biochemical, and anatomical determinants were assessed in 10 resurrection species from diverse locations, including ferns, and homoiochlorophyllous and poikilochlorophyllous angiosperms. Data obtained were compared with previously published results in desiccation-sensitive ferns and angiosperms. A n in resurrection plants was mostly driven by mesophyll conductance to CO2 ( g m ) and limited by CO2 diffusion. Resurrection species had a greater cell wall thickness ( T cw ) than desiccation-sensitive plants, a feature associated with limited CO2 diffusion in the mesophyll, but also greater chloroplast exposure to intercellular spaces ( S c ), which usually leads to higher g m . This combination enabled a higher A n per T cw compared with desiccation-sensitive species. Resurrection species possess unusual anatomical features that could confer stress tolerance (thick cell walls) without compromising the photosynthetic capacity (high chloroplast exposure). This mechanism is particularly successful in resurrection ferns, which display higher photosynthesis than their desiccation-sensitive counterparts. Abstract : Photosynthesis measurements in 10 resurrection fern and angiosperm species show how these desiccation-tolerant species compensate the CO2 diffusion limitation of their thick cell walls by chloroplast exposure in the mesophyll.